Current status and future prospects of molecular imaging in targeting the tumor immune microenvironment - Wang, Xiang; Shen, Weifen; Yao, Lingjun; Li, Chao; You, Huiming; Guo, Duancheng (Frontiers in Immunology, 2025)
Molecular imaging technologies have significantly transformed cancer research and clinical practice, offering valuable tools for visualizing and understanding the complex tumor immune microenvironment. These technologies allow for the non-invasive examination of key components within the tumor immune microenvironment, including immune cells, cytokines, and stromal cells, providing crucial insights into tumor biology and treatment responses. This paper reviews the latest advancements in molecular imaging, with a focus on its applications in assessing interactions within the tumor immune microenvironment. Additionally, the challenges faced by molecular imaging technologies are discussed, such as the need for highly sensitive and specific imaging agents, issues with data integration, and difficulties in clinical translation. The future outlook emphasizes the potential of molecular imaging to enhance personalized cancer treatment through the integration of artificial intelligence and the development of novel imaging probes. Addressing these challenges is essential to fully realizing the potential of molecular imaging in improving cancer diagnosis, treatment, and patient outcomes.